The Timing of Reproduction is Responding Plastically, not Genetically, to Climate Change in Yellow-Bellied Marmots (Marmota flaviventer) - St Lawrence, Sophia Helen (Université d'Ottawa / University of Ottawa, 2022)
With global climates changing rapidly, animals must adapt to new environmental conditions with altered weather and phenology. Key to adapting to these new conditions is adjusting the timing of reproduction to have offspring when the conditions are best to maximize growth and survival. Using a long-term dataset on a wild population of yellow-bellied marmots (Marmota flaviventer) at the Rocky Mountain Biological Laboratory (RMBL), we investigated how the timing of reproduction changed with changing spring conditions over the past 50 years. Marmots are hibernators with a four-month active season. It is thus crucial to reproduce early enough in the season to have time to prepare for hibernation, but not too early so as snow cover prevents access to food. Importantly, climate change in this area has increased spring temperatures by 5 °C and decreased spring snowpack by 50 cm over the past 50 years. This directional change in climate may have caused adaptation. Given that adaptation to environmental conditions could arise from either microevolution or phenotypic plasticity, we evaluated how female marmots adjust the timing of their reproduction and estimated the importance of both genetic variance and plasticity in the variation in this timing. We show that, within a year, the timing of reproduction is not as tightly linked to the date a female emerges from hibernation as previously thought. We report a positive effect of spring snowpack but not of spring temperature on the timing of reproduction. There is inter-individual variation in the timing of reproduction but not in its response to changing spring conditions. Genetic variance in the timing of reproduction is low, and heritability was 8%. Earlier pup emergence date increases the number and weighted proportion of pups surviving their first winter, indicative of directional selection on this trait. The same pattern is not found for litter size with no effect of pup emergence date on the number of pups born. Further, all three of these traits are not under stabilizing selection. Taken together, it seems that we should expect some changes in this population with changing climatic conditions, but because of plasticity and not due to natural selection. Further, future studies on the marmots should not operate under the assumption that females reproduce immediately following their emergence.
Keywords: Microevolution; Phenotypic Plasticity; Climate Change; Evolutionary Ecology